ASYMMETRY IN STOCK VOLATILITY FOR THE FOX INDEX AND ITS COMPONENTS - Repo, Timo (My University, 2005)
The purpose of the thesis is to study the behavior of volatility on Finnish stock market during period 1997-2001. Emphasis is on volatility response between positive and negative returns and volatility asymmetry. In the theoretical chapters capital markets, volatility and Value at Risk (VaR) are introduced. The sample used in the empirical examination consists of 43 companies, which were at some stage a member of the FOX index at HEX during the research period. The volatility processes of the FOX index and all its constituent stock are compared after estimating ARCH models from four years of daily returns, from 1997 to 2000. The index and the majority of the stocks have a greater volatility response to negative returns than to positive returns and the asymmetry is slightly higher for the index than for most stock. Possible explanation for the high level asymmetry of index is covariance asymmetry. The implications of volatility asymmetry are obvious. During the periods of higher volatility, it becomes more attractive to withdraw from the stock market and invest on risk-free instruments, such as government bonds etc. In addition, a reasonable investor could benefit by following a strategy based on fact that differences exist in volatility between negative and positive returns on the stock market.
Keywords: Volatility; ARCH model; Value-at-Risk (VaR); Capital Markets; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|